Universal Physical Laboratory Supports - Central Scientific Company (Physical Apparatus for Universities and Colleges Manufactured and Imported by Central Scientific Co., 1912)
Illustration of possible combinations of laboratory equipment on the "Universal Physical Laboratory Supports." Part of Catalog K: Physical Apparatus for Universities and Colleges, a catalog of laboratory instruments for the physical sciences made by the Central Scientific Company. Founded in 1900 in downtown Chicago, Central Scientific manufactured and distributed science teaching equipment for schools, colleges, and universities by catalog mail order. The trademark CENCO was used from 1909 onwards.
Keywords: Scientific apparatus and instruments; Laboratories--Equipment and supplies; Universities and colleges